Pengaruh Likuiditas Dan Leverage Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Sub Sektor Farmasi Di Bursa Efek Indonesia - Febrika Nurfianti; Dewi Sutjahyani (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study examines pharmaceutical companies—business entities engaged in the research, development, production, and distribution of medicines, vaccines, supplements, and other healthcare products—listed on the Indonesia Stock Exchange during the 2021–2024 period. The study aims to analyze the effect of liquidity and leverage on firm value, with profitability serving as an intervening variable. The analysis using the PLS-SEM method indicates that: (1) liquidity has no significant effect on profitability; (2) leverage has a negative and significant effect on profitability; (3) liquidity has no significant effect on firm value; (4) leverage has no significant direct effect on firm value; (5) profitability has no significant effect on firm value; and (6) profitability does not mediate the relationship between liquidity and leverage and firm value. These findings indicate that in the context of the Indonesian pharmaceutical industry, investor valuation is not based solely on historical profit performance or short-term liquidity conditions. Investors tend to place greater emphasis on long-term strategic factors unique to the pharmaceutical sector, such as research and development (R&D) pipelines, product portfolio strength, market expansion strategies, and resilience to regulatory environments. The implications suggest that pharmaceutical company management should be more cautious in taking on debt due to its negative impact on profitability and should more actively communicate long-term strategies and non-financial value drivers to the market.